Binding interactions of the peripheral stalk subunit isoforms from human V-ATPase. Issue 5 (3rd May 2016) - Rahman, Suhaila; Yamato, Ichiro; Saijo, Shinya; Mizutani, Kenji; Takamuku, Yuuki; Ishizuka-Katsura, Yoshiko; Ohsawa, Noboru; Terada, Takaho; Shirouzu, Mikako; Yokoyama, Shigeyuki; Murata, Takeshi
Abstract: The mammalian peripheral stalk subunits of the vacuolar-type H + -ATPases (V-ATPases) possess several isoforms (C1, C2, E1, E2, G1, G2, G3, a1, a2, a3, and a4), which may play significant role in regulating ATPase assembly and disassembly in different tissues. To better understand the structure and function of V-ATPase, we expressed and purified several isoforms of the human V-ATPase peripheral stalk: E1G1, E1G2, E1G3, E2G1, E2G2, E2G3, C1, C2, H, a1NT, and a2NT . Here, we investigated and characterized the isoforms of the peripheral stalk region of human V-ATPase with respect to their affinity and kinetics in different combination. We found that different isoforms interacted in a similar manner with the isoforms of other subunits. The differences in binding affinities among isoforms were minor from our in vitro studies. However, such minor differences from the binding interaction among isoforms might provide valuable information for the future structural-functional studies of this holoenzyme. Graphical abstract: : Schematic model of human V-ATPase illustrating the mode of binding interactions at the peripheral stalk region.